2015
DOI: 10.1080/15592324.2014.1001225
|View full text |Cite
|
Sign up to set email alerts
|

Potential ecological roles of flavonoids fromStellera chamaejasme

Abstract: Stellera chamaejasme L. (Thymelaeaceae), a perennial weed, distributes widely in the grasslands of Russia, Mongolia and China. The plant synthesizes various secondary metabolites including a group of flavonoids. To our knowledge, flavonoids play important roles in the interactions between plants and the environment. So, what are the benefits to S. chamaejasme from producing these flavonoids? Here, we discuss the potential ecological role of flavonoids from S. chamaejasme in protecting the plant from insects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Stellera chamaejasme L. (Thymelaeaceae), a perennial weed, is distributed widely across the grasslands of Russia, Mongolia and China (Shirai et al, ; Yan et al, ; Yan, Zeng, Jin, & Qin, ). Its roots are commonly known as ‘Ruixianglang du’ in Chinese, and have been used in China as a traditional Chinese medicine for the treatment of scabies, tinea, stubborn skin ulcers, chronic tracheitis, cancer and tuberculosis (Xu, Qin, Li, & Xu, ; Zhang et al, ; Pan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Stellera chamaejasme L. (Thymelaeaceae), a perennial weed, is distributed widely across the grasslands of Russia, Mongolia and China (Shirai et al, ; Yan et al, ; Yan, Zeng, Jin, & Qin, ). Its roots are commonly known as ‘Ruixianglang du’ in Chinese, and have been used in China as a traditional Chinese medicine for the treatment of scabies, tinea, stubborn skin ulcers, chronic tracheitis, cancer and tuberculosis (Xu, Qin, Li, & Xu, ; Zhang et al, ; Pan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, see [65], presented lavonoids as are at least partly responsible for the strong phytotoxic efects of Stellera chamaejasme L. The potential allelopathic behavior may facilitate this weed to become a good competitor against other plant species in the environment.…”
Section: Allelopathymentioning
confidence: 92%
“…Some lavonoids present a level of phytotoxicity, indicating that allelopathy could be a beneicial function of the lavonoids to the producing plant [65]. Although the relative role of lavonoids in allelopathic interference has been less well-characterized than of some secondary metabolites, some examples of their involvement in autotoxicity and allelopathy are reported…”
Section: Allelopathymentioning
confidence: 99%
“…Here, we sorted the studies done under both laboratory and field conditions, and found that the primary phytotoxic mechanisms were regulated via the following two pathways. First, allelochemicals (e.g., flavonoids, coumarins, and phenolic compounds) can inhibit mitosis (Yan et al, 2016), reduce chlorophyll content (Pan, Li, Yan, Guo, & Qin, 2015), disrupt root development (Yan et al, 2014), promote the overproduction of proline (Yan et al, 2016), inhibit germination (Cheng et al, 2011), reduce endogenous auxin content (Yang et al, 2011), and promote reactive oxygen species accumulation (Pan et al, 2015;Yan, Zeng, Jin, & Qin, 2015).The second pathway is the arrest of sexual multiplication by pollen allelopathy (Sun, Luo, & Wu, 2010). Interestingly, phytotoxic effects increase with age; that is, older plants are superior competitors compared with younger plants (Wei, Zhong, Xu, Du, & Sun, 2017).…”
Section: Interspecific Relationshipsmentioning
confidence: 99%
“…(a) plants of S. chamaejasme in an alpine grassland; (b) plants of S. chamaejasme in a typical grassland; (c) S. chamaejasme outside the fence; (d) white flower of S. chamaejasme; (e) landscape of S. chamaejasme in an alpine grassland; (f) landscape pattern of S. chamaejasme in a desert grassland taken by an unmanned aerial vehicle , insect pests, and fungal pathogens(Barillas, Paschke, Ralphs, & Child, 2007;Jin et al, 2013). Furthermore, the toxic compounds of these weeds are capable of poisoning or killing small rodents and play a vital role in protecting toxic weeds from animals and pathogens(Yan et al, 2015). The content of toxic substances is highest in leaves, which is the vegetative organ most likely to be consumed by herbivores.…”
mentioning
confidence: 99%